Expressions of serum fibroblast growth factor-23/anti-aging gene Klotho, helper T lymphocyte 1/helper T lymphocyte 2 cytokines in elders with end-stage renal disease and their impacts on the prediction and prognosis of hospital-acquired infection - Xia Ye; Li-wei Yang; Xue-mei Cai; Qiu-hong Tang; Cheng-mao Zhang (Editorial Department of Journal of Clinical Nephrology, 2024)
ObjectiveTo observe the expression of serum fibroblast growth factor 23 （FGF23）/anti-aging gene Klotho and helper T lymphocyte （Th） 1/Th2 cytokines in elders with end-stage renal disease （ESRD） and analyze their impact on the prediction and prognosis of hospital-acquired infection. Methods From January 1, 2021 to December 31, 2022, 106 ESRD elders hospitalized into Zigong Mental Health Center （Zigong Geriatric Hospital） were recruited. There were 65 males with an average age of （67.21±3.07）（60-84） year and 41 females with an average age of （67.65±2.98）（60-84） year. Serum levels of FGF23, Klotho, Th1 cytokines [interferon-gamma （IFN-γ） & interleukin-2 （IL-2）] and Th2 cytokines （IL-4 & IL-10） were measured at Day 2 post-admission, acute physiology & chronic health status scoring system II （APACHE II） was evaluated. According to whether or not hospital-acquired infection occurred during hospitalization, they were assigned into two groups of infection （n=28） and non-infection （n=78）. Various serum parameters and APACHE II scores of two groups were compared and the correlation between each parameter and APACHE II score was analyzed. Survival status was statistically analyzed after a 3-month follow-up. Serum levels of FGF23, Klotho, IFN-γ, IL-2, IL-4 and IL-10 were compared among patients with different prognoses. Predictive value and clinical utility of each indicator for hospital infection and prognosis were analyzed. Results A total of 106 ESRD elders were divided into two groups of infection （n=28） and non-infection （n=78） based upon whether or not hospital-acquired infection occurred during hospitalization. After a follow-up period of 3 months, 71 patients survived and 35 patients died. At Day 2 post-admission, serum levels of FGF23, IL-4, IL-10 and APACHE II scores were （78.64±20.16） ng/mL, （20.14±1.48） μg/L, （22.47±2.56） μg/L and （26.38±6.51） points in infection group versus （60.17±16.83） ng/mL, （16.25±1.21） μg/L, （19.52±1.86） μg/L and （22.97±6.45） points in non-infection group. Serum levels of FGF23, IL-4, IL-10 and APACHE II scores were higher in infection group than those in non-infection group （P＜0.05）. At Day 2 post-admission, serum levels of Klotho, IFN-γ and IL-2 were （34.95±12.62） ng/mL, （22.19±1.69） μg/L and （28.73±2.95） μg/L in infection group versus （51.61±16.08） ng/mL, （25.31±1.74） μg/L and （33.95±1.52） μg/L in non-infection group. Serum levels of Klotho, IFN-γ and IL-2 in infection group were lower than those in non-infection group （P＜0.05）. Serum levels of FGF23, IL-4 and IL-10 were correlated positively with APACHE II score （correlation coefficients r=0.629, 0.597 and 0.612, all P＜0.05） while serum levels of Klotho, IFN-γ and IL-2 negatively with APACHE II score （correlation coefficients r=−0.632, −0.718, −0.701 and 0.597, all P＜0.05）. Serum levels of FGF23, IL-10 and IL-4 were （77.49±21.85） ng/mL, （24.76±4.77） μg/L and （24.81±6.28） μg/L in deceased patients versus （58.92±16.94） ng/mL, （18.10±3.82） μg/L and （13.57±4.38） μg/L in survivors. Serum levels of FGF23, IL-10 and IL-4 were higher in deceased patients than those in survivors at Month 1 post-enrollment （P＜0.05）. At Month 1 post-enrollment, serum levels of Klotho, IFN-γ and IL-2 were （30.03±11.76） ng/mL, （20.33±2.63） and （27.19±4.91） μg/L in deceased patients versus were （55.68±17.02） ng/mL, （26.54±4.79） μg/L and （35.22±5.64） μg/L in survivors. Serum levels of Klotho, IFN-γ and IL-2 were lower in deceased patients than those in survivors （P＜0.05）. The areas under receiver operating characteristic （ROC） curve for serum levels of FGF23, Klotho, IFN-γ, IL-2, IL-4 and IL-10 in predicting the occurrence of hospital infection and survival status in ESRD patients were 0.904 （OR: 0.832-0.953） and 0.911 （OR: 0.840-0.958） with excellent clinical utilities （P＜0.05）. Conclusion In ESRD elders, an imbalance of serum FGF23/Klotho and Th1/Th2 cytokine levels, abnormal elevations in serum levels of FGF23, IL-10 and IL-4 and lower serum levels of Klotho, IFN-γ and IL-2 are highly predictive of hospital-acquired infection and prognosis.